2001
DOI: 10.1034/j.1600-051x.2001.028006565.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthesis is decreased in periodontitis

Abstract: Local NO production is decreased in patients with periodontitis. This effect is more pronounced in those with severe types of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 18 publications
6
55
2
5
Order By: Relevance
“…This result is similar to other studies that have shown increased levels of amino acids related to NO in periodontal disease (11), increased expression Table 1 Concentration of NO in saliva samples subjected to the Griess Reaction of iNOS in periodontal disease biopsy samples (25)(26)(27), as well as in gingival fibroblast cell cultures (12,28). In contrast, one report has described a reduction of salivary NO levels in individuals with adult periodontitis and with aggressive periodontitis (29). This report is in disagreement with the vast majority of the literature that describes increased levels of NO in periodontal disease (5,(30)(31)(32).…”
Section: Discussioncontrasting
confidence: 34%
“…This result is similar to other studies that have shown increased levels of amino acids related to NO in periodontal disease (11), increased expression Table 1 Concentration of NO in saliva samples subjected to the Griess Reaction of iNOS in periodontal disease biopsy samples (25)(26)(27), as well as in gingival fibroblast cell cultures (12,28). In contrast, one report has described a reduction of salivary NO levels in individuals with adult periodontitis and with aggressive periodontitis (29). This report is in disagreement with the vast majority of the literature that describes increased levels of NO in periodontal disease (5,(30)(31)(32).…”
Section: Discussioncontrasting
confidence: 34%
“…38,39 Furthermore, same studies reported that, polymorphonuclear leukocytes isolated from gingival pockets have a stronger suppressive effect on NO production than polymorphonuclear leukocytes from venous blood. However, Aurer et al 40 reported that, it is not clear whether decreased NO in periodontal disease is simply a marker of increased inflammatory activity and tissue destruction or whether it is causative in the pathogenesis of the periodontal disease.…”
Section: Inflammation;mentioning
confidence: 99%
“…During orthodontic tooth movement, remodeling which involves tissue damage and new tissue formation in the same time around the tooth alveolar bone, 40,41 periodontal ligament 42,43 and gingival tissues occur. 42 Moreover orthodontic tooth movement has similar properties with inflammation and wound healing.…”
Section: Application Of Force On Tooth;mentioning
confidence: 99%
“…The amount Nitrogen oxides accumulated in the dental biofilm depends on the amount of nitrate in the food consumed. Nitric oxide oxidation would be another source for nitrogen oxides production in saliva [16]. In case the plaque pH level remains low for ling time, this would lead to the accumulation of high percentage of nitrogen oxide in dental biofilm.…”
Section: Denitrification Effect On the Progression Of Periodontal Dismentioning
confidence: 99%
“…This would be the reason why nitrogen oxides are significantly higher in poor oral hygiene individuals than those with good oral hygiene who have thinner dental biofilm [22]. Many anaerobic facultative bacteria synthesize nitrate reductase in low oxygen tension [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], hence, reduction can take place in the thick biofilm or deep tongue crypts [23]. In thick cariogenic plaque, the low pH level allows the production of acidified nitrite.…”
Section: Denitrification Effect On Dental Caries Formationmentioning
confidence: 99%